TANTANGAN IMPLEMENTASI PROYEK P5 DI SDN BELITUNG SELATAN 1: PERBEDAAN PEMAHAMAN ANTARA SEKOLAH DAN ORANG TUA - Rahmi Nur ‘Aini; Shopia Nabila; Fa'izah, Nurul; Siti Nor Shahada; Aslamiah; Diani Ayu Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Curriculum development in elementary schools is very important in ensuring better quality education. This study aims to understand how SDN Belitung Selatan 1 implements the curriculum and the challenges faced in the process. The research method used was an interview with the principal as the main informant. The results of the study showed that the implementation of the curriculum was carried out in stages from 2020 to 2024, with various obstacles faced, such as differences in implementation stages between classes, limited time for teachers to study the curriculum, and challenges in implementing the Pancasila Student Profile Strengthening Project (P5). Several solutions have been implemented, such as the formation of teacher study groups, socialization to parents, and periodic evaluation of curriculum implementation. With these efforts, the implementation of the curriculum can run more effectively even though there are still obstacles that need to be overcome.